Derivatives of Various Inverse Functions

Learning Outcomes

  • Calculate the derivative of an inverse function

We begin by considering a function and its inverse. If f(x) is both invertible and differentiable, it seems reasonable that the inverse of f(x) is also differentiable. Figure 1 shows the relationship between a function f(x) and its inverse f1(x). Look at the point (a,f1(a)) on the graph of f1(x) having a tangent line with a slope of (f1)(a)=pq. This point corresponds to a point (f1(a),a) on the graph of f(x) having a tangent line with a slope of f(f1(a))=qp. Thus, if f1(x) is differentiable at a, then it must be the case that

(f1)(a)=1f(f1(a))

 

This graph shows a function f(x) and its inverse f−1(x). These functions are symmetric about the line y = x. The tangent line of the function f(x) at the point (f−1(a), a) and the tangent line of the function f−1(x) at (a, f−1(a)) are also symmetric about the line y = x. Specifically, if the slope of one were p/q, then the slope of the other would be q/p. Lastly, their derivatives are also symmetric about the line y = x.

Figure 1. The tangent lines of a function and its inverse are related; so, too, are the derivatives of these functions.

We may also derive the formula for the derivative of the inverse by first recalling that x=f(f1(x)). Then by differentiating both sides of this equation (using the chain rule on the right), we obtain

1=f(f1(x))(f1)(x))

 

Solving for (f1)(x), we obtain

(f1)(x)=1f(f1(x))

 

We summarize this result in the following theorem.

Inverse Function Theorem


Let f(x) be a function that is both invertible and differentiable. Let y=f1(x) be the inverse of f(x). For all x satisfying f(f1(x))0,

dydx=ddx(f1(x))=(f1)(x)=1f(f1(x))

 

Alternatively, if y=g(x) is the inverse of f(x), then

g(x)=1f(g(x))

 

Example: Applying the Inverse Function Theorem, 1

Use the Inverse Function Theorem to find the derivative of g(x)=x+2x. Compare the resulting derivative to that obtained by differentiating the function directly.

Watch the following video to see the worked solution to Example: Applying the Inverse Function Theorem, 1.

Try It

Use the inverse function theorem to find the derivative of g(x)=1x+2. Compare the result obtained by differentiating g(x) directly.

Hint

Use the preceding example as a guide.

Example: Applying the Inverse Function Theorem, 2

Use the inverse function theorem to find the derivative of g(x)=x3.

Try It

Find the derivative of g(x)=x5 by applying the inverse function theorem.

From the previous example, we see that we can use the inverse function theorem to extend the power rule to exponents of the form 1n, where n is a positive integer. This extension will ultimately allow us to differentiate xq, where q is any rational number.

Extending the Power Rule to Rational Exponents


The power rule may be extended to rational exponents. That is, if n is a positive integer, then

ddx(x1/n)=1nx(1/n)1

 

Also, if n is a positive integer and m is an arbitrary integer, then

ddx(xm/n)=mnx(m/n)1

 

Proof

The function g(x)=x1/n is the inverse of the function f(x)=xn. Since g(x)=1f(g(x)), begin by finding f(x). Thus,

f(x)=nxn1 and f(g(x))=n(x1/n)n1=nx(n1)/n.

 

Finally,

g(x)=1nx(n1)/n=1nx(1n)/n=1nx(1/n)1.

 

To differentiate xm/n we must rewrite it as (x1/n)m and apply the chain rule. Thus,

ddx(xm/n)=ddx((x1/n)m)=m(x1/n)m11nx(1/n)1=mnx(m/n)1.
◼

Example: Applying the Power Rule to a Rational Power

Find the equation of the line tangent to the graph of y=x23 at x=8.

Watch the following video to see the worked solution to Example: Applying the Power Rule to a Rational Power.

Try It

Find the derivative of s(t)=2t+1.

Try It